Clinical etiological evaluation of Pancytopenia: Experience of tertiary care teaching hospital in central India - Preeti Negotia; Rita Singh Saxena; R. S. Jagat; T. N. Dubey (International Journal of Medical Research and Review, 2017)
Introduction: Pancytopenia is a common clinico-hematological entity. There are significant variations in incidence of disorders causing pancytopenia.Objectives: To evaluate different causes of pancytopenia & to correlate underlying etiology of pancytopenia with clinical profile.Methods: This prospective observational study was done in the Department of Medicine, Gandhi Medical College & Hamidia Hospital, Bhopal between July 2014 to Nov. 2015. 70 cases of pancytopenia were included. All participants underwent clinical evaluation and baseline investigations followed by bone marrow examination.Result: Out of 70 patients, 71% were < 40 years and male to female ratio of 1.41:1. Most common presentation was fever and weakness. Most common physical findings were splenomegaly seen in 48 cases. Lymphadenopathy was noted in 6 cases. Megaloblastic anaemia (41.4%) was most common cause of pancytopenia irrespective of age and sex. It was followed by aplastic anaemia, hypersplenism and leukaemia. Together these four accounted for 94.3% cases. In younger patients common causes after megaloblastic anemia (42.9%) were aplastic anemia followed by leukemia, hypersplenism, autoimmunity and infection. In older age group common causes were hypersplenism (23.8%), aplastic anemia, leukemia and infection after megaloblastic anemia. Aplastic anemia was more common in males and hypersplenism in females.Conclusion: In our study megaloblastic anemia is most common cause of pancytopenia in this part of India irrespective of age and gender. Splenomegaly was more common in megaloblastic anemia, hypersplenism and malignancies. Most of the patients without splenomegaly had aplastic anemia.